KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN KEBIJAKAN DIVIDEN (Perusahaan Sektor Industri Barang Konsumsi Di Bursa Efek Indonesia) - Tantri Cahyaning Amalia; Siti Nurlaela; Riana Rachmawati Dewi (Among Makarti, STIE AMA Salatiga, 2020)
Abstract This study aims to analyze the factors affecting the dividend payment policy which was presented with Dividend Payout Ratio (DPR). The independent variables include managerial ownership, institutional ownership, profitability (Return on Assets), leverage (Debt to Equity Ratio) and liquidity (Current Ratio). This research was conducted in the consumer goods industry companies listed on the Stock Exchange in 2013-2018. The samples used are 9 companies. The sampling method using purposive sampling. Data analysis technique used is multiple linear regression. The results showed that the profitability (Return on Assets) and leverage (Debt to Equity Ratio) have effect on dividend policy. While the managerial ownership, institusional ownership, and liquidity (Current Ratio) that have no effect on dividen policy. Keywords: Ownership, Profitability, Leverage, Liquidity, Dividend